The Implicit Conception of Conscience Hold by Teachers of Ethics - Vaicekauskienė, Vaiva (Acta Paedagogica Vilnensia, 2003)
The article presents the problem of implicit conception of conscience that may influence the hidden curriculum, and the results of empirical investigation of this conception. The research was based on the analysis of autobiographical narratives of moral development, written by teachers of ethics (114 respondents). Four aspects were taken into account: the context or moral consciousncss, the concept of moral development. Moral content of narratives and emotional connotation. The context was analysed looking for the main themes in the first sentences of narratives. Prevailing context are members of family and families way of life in respondents childhood. Less frequent is introducing of personal characteristics. Some discuss whether their childhood was happy or not. Some present the story of conscience as the story of problems, painful or shameful experience. Conclusions about the concept of development of conscience were based on analysis of the structure of narratives. There were found three types of them: mosaic (authors tell about.fi1cts or persons), purposefully developed (chronological processes are described) and of mixed structure. Analysis of the moral content of narratives revealed that teachers are inclined to remember personal guilts (51 % of events that were described) and negative experience (75.2% of events). The most frequent contcnt of moral dilemmas is theft (28.1%), consciousness (19.5%) and respect/humiliation (17.8%). Prevailing emotional connotation of moral reminiscents is negative: shame (29.2% ), fear (23.2% ), pain (12.4 % ), pity (9.2 %), and sadness (9.2% ). The results show that teachers of ethics are inclined to associate conscience with authoritarian repressive paradigm. That may cause psychological barriers to discuss the topic of conscience at the lessons.
Keywords: conscience; moral self - consciousness; implicit conception; moral education; hidden curriculum